Mode of Response Students’ Engagement (MORSE): Basis for Improving Science Performance of Students - Arzadon, Eleazer (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
In educational system, just like in a classroom setting, there is a degree or sense of uncertainty or ambiguity on how teaching-learning process will take place. It is the duty and responsibility of the teacher to structure the classroom in maximizing students learning by engag-ing in all modalities such as hearing, visual, olfactory, kinesthetic and gustatory. Moreover, by bringing students together in the classroom to produce group interaction that facilitates learning in different in-dividuals.I, the Researcher, had facilitated an active learning through the use of Mode of Response for Students Engagement (MORSE). Inter-vention was the use of personalized card, dyad, work cell group and random calling conducted twice a week for the duration of the 1st grading period. The 29 respondents from experimental group were subjected to MORSE and 29 respondents from control group were given traditional classroom engagement. The proponent sought to answer the following research questions: What was the effect on the academic performance of the students who were subjected to MORSE? Was there a significant difference in the pre-test and post-test result using the traditional method and of the MORSE method? Lastly, what was the implication of MORSE method in teaching Earth Science among grade 10 students?The collected data of pre-test and post-test results were gathered and treated using paired sample t-test of difference and mean. Sample paired t-test result showed that the computed t value of 7.45 is greater than the t critical value of 1.701 at level of significance of 0.05. There is significant difference on the post test result between the con-trol group and experimental group. The Experimental group, who were subjected to MORSE techniques achieved higher post-test than the control group. Based from the analysis gathered, MORSE methods is highly effective as means of engaging students to actively partici-pate and improve academic performance in Earth Science. Therefore, I, the proponent recommended the use of MORSE in classroom activities. Likewise, teachers can make use other MORSE techniques or devices to facilitate active learning in the classroom for whole class engagement.